Production, nutritive value and estimated milk yield from intercropped pastures of cold season Produção, valor nutritivo e produtividade estimada de leite de pastagens consorciadas de estação fria - Barreta D.A.* (2020)
© 2020 Universidade Federal de Minas Gerais.The objective of this work was to evaluate the potential of milk production ha-1 of three consortia of black oats and legumes in detriment to black oats fertilized with N mineral. The treatments used were black oats + 200kg of N ha-1 (Av+N); black oats + white clover (Av+Tb); black oats + vetch (Av+Er) and black oats + red clover (Av+Tv). The species were implanted in 80 m2 plots under a complete randomized complete block design with four replicates. Samples were collected three times and the material evaluated was dry matter yield, chemical and bromatological composition (CP, EE, NDF, ADF, NFC, MM, estimated dry matter digestibility and NDF digestibility in 48 hours) and estimated milk production by area (kg ha-1). The results were submitted to analysis of variance and the means were compared by Tukey test at 5% probability. The chemical-bromatological composition did not differ between Av+N and Av+Er treatments in any of the evaluated attributes. The Av+Er treatment provided higher milk yield per area in relation to the others, explained by the higher DM production.